EDUCATIONAL MANAGEMENT MODEL OF DARUL ISTIQAMAH ISLAMIC BOARDING SCHOOL MAKASSAR - Dewi Asmia Nur; Suci foura; Arismunandar; Yunita Rezky Dati Ali; Ahlun ansar (BAIK Publishers, 2025)
This article aims to analyze the education and coaching system at the Darul Istiqamah Islamic Boarding School in Makassar, as well as the role of Kiai and teachers in managing students. This study uses a descriptive qualitative method, involving interviews, observations, and documentation to obtain in-depth data on aspects of education in Islamic boarding schools. The results of the study indicate that the Darul Istiqamah Islamic Boarding School applies a holistic approach in fostering the character and religious knowledge of students. The role of Kiai and teachers is very significant in directing and guiding students through interactive and participatory teaching methods. In addition, this study identifies the challenges faced in the process of accepting students and organizing their social lives. The conclusion of this study confirms that the Darul Istiqamah Islamic Boarding School is committed to improving the quality of education by maintaining local religious and cultural values, and adapting to the times. The existence of this Islamic boarding school not only contributes to religious education, but also to the formation of the character of students who have noble morals and are ready to contribute positively to society.